[Cu(H2btec)(Bipy)]?: Reusable Metal Organic Polymer Catalyst for Epoxidation Reactions - Venegas-Yazigi, D; Venegas-Yazigi, D (Wiley-VCH Verlag, 2011)
The search of new inorganic materials with better catalytic properties is an important field of research. Reusability, efficiency and atom economy correspond to the main parameters to characterize a catalyst. In this work, we inform the effectiveness of [Cu(H2btec)(bipy)]? (H4btec = 1,2,4,5-benzenetetracarboxylic acid) as an heterogeneous coordination polymer catalyst for the oxidation of olefins. The catalyst exhibits good atom economy, high turnover numbers and good selectivity for a ratio of 4000/1 substrate/catalyst for cyclohexene and styrene oxidation. Furthermore, the catalyst was recycled and reused for seven consecutive cycles, retaining the structural integrity and effectiveness as catalyst in all the performed experiments. Copyright © 2011 WILEY-VCH Verlag GmbH & Co. KGaA, Weinheim.